Faktor Penentu Pengungkapan Informasi Laporan Keuangan melalui Laman Internet: Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Soepriyanto, Gatot; Dustinova, Dustinova (Binus Business Review, 2012)
The study aims to investigate the factors affecting companies to disclose financial statement information through internet (internet financial reporting). Assessment of the disclosure uses 29 criteria as used by Abdelsalam et al (2007). The method of testing hypotheses in this study is the linear regression method by comparing the extensive disclosure of financial statements on the internet as the dependent variable and type of industry, firm size, profitability, leverage levels and types of auditors as independent variables. Through the observation 69 listed companies in the KOMPAS100 directory, the study concluded that 59.17% of companies meet the criteria for such disclosure made by Abdelsalam et al (2007). Consistent with some previous studies, factors that play an important role on the level of disclosure is the companys size and corporate profitabilty.